2021
DOI: 10.1016/j.jhazmat.2021.125658
|View full text |Cite
|
Sign up to set email alerts
|

Can ozone inactivate SARS-CoV-2? A review of mechanisms and performance on viruses

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has challenged societies around the globe. Technologies based on ozone, a powerful oxidant, have been evaluated to inactivate this virus in aerosols and fomites. However, the high data diversity hinders the possibility of establishing a common ground for determining best practices for the use of these technologies. Furthermore, there is a lack of consensus regarding which are the main mechanisms of ozone virus inactivation. This critical rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 67 publications
2
69
0
1
Order By: Relevance
“…Beside the different surrogates employed as models for SARS-CoV-2 in previous studies, viral inactivation is undoubtedly dose-dependent. However, for application purposes it is notably to underline that relative humidity plays a key role in enhancing O 3 mediated inactivation, as the higher RH the more virus is inactivated (data not shown, [15] , [18] ). Thus, specific assays are needed to bring to light how and at which extent RH affects the viral inactivation rates in field tests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beside the different surrogates employed as models for SARS-CoV-2 in previous studies, viral inactivation is undoubtedly dose-dependent. However, for application purposes it is notably to underline that relative humidity plays a key role in enhancing O 3 mediated inactivation, as the higher RH the more virus is inactivated (data not shown, [15] , [18] ). Thus, specific assays are needed to bring to light how and at which extent RH affects the viral inactivation rates in field tests.…”
Section: Resultsmentioning
confidence: 99%
“…Recently the virucidal efficacy of the ozone has been reviewed considering the best environmental condition, i.e. temperature and humidity, the ozone concentration and contact times, for a broad number of independent viruses [18] . The ozone could be an efficient potential disinfectant against the SARS-CoV-2 because his lipid envelope can be readily degraded by ozone [14] , [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ozone [ 18 ] and hypochlorous acid [ 19 ] damage viral proteins, genomes and lipid layers of biological membranes, such as the viral envelope. Alcohols show more substantial virucidal activity against enveloped viruses than non-enveloped viruses, suggesting that the viral lipid envelope is a potential target of EtOH [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…can deactivate the enveloped viruses via the oxidation of thiol groups in virus proteins and denaturation of proteins. [ 42 , 43 , 44 , 45 ] Similarly, iodophors can release iodine which can penetrate into the membrane and oxidize the proteins’ thiols and also damage the RNA of the virus. Therefore, tethering of the safe oxidizing agents on the surface of personal protection equipment (PPE) can be used as an appropriate approach for fabrication of antiviral PPEs.…”
Section: Surface Stabilities and Decontamination Of Sars‐cov‐2mentioning
confidence: 99%